Coupled Inductor Based High Step-up Hybrid Inverter for Microgrid Application - Ahmad A.; Shiluveru K.; Singh R.K.; Beig A.R. (My University, 2025)
Presence of right half plane zero (RHPZ) in conventional boost and buck-boost derived hybrid converters makes the system non minimum phase and it becomes difficult to obtain adequate phase margin along with higher bandwidth for such systems. Moreover, for microgrid applications, these need to operate on very high duty ratio in order to obtain high voltage gain, which causes severe reverse recovery of the diodes and increased EMIs. This paper introduces a high step-up hybrid inverter having no RHPZ for hybrid microgrid. The proposed hybrid inverter is developed by coupling the filter inductors of a quadratic boost converter with an insertion of damping network in the circuit and replacing the load side main switch by the H-bridge inverter. This arrangement helps in complete elimination of RHPZ and thereby makes the system minimum phase. The proposed hybrid inverter gives high step-up de voltage with comparatively low duty ratio and also provides simultaneous AC and DC outputs with inherent shoot through protection. Detailed mathematical modeling and small signal dynamic analysis are carried out. Experimental and simulation results are presented to validate the proposed hybrid inverter for the hybrid microgrid. © 2019 IEEE.